TRAFFICKING MECHANISMS AND DIAGNOSTIC ADVANCEMENTS IN CWD - Cole, Jesse Daniel Mayers, author; Mathiason, Candace, advisor; Ruder, Mark, committee member; Olver, Christine, committee member; Dobos, Karen, committee member; Barfield, Jennifer, committee member (Colorado State University. Libraries, 2026)
ABSTRACT TRAFFICKING MECHANISMS AND DIAGNOSTIC ADVANCEMENTS IN CWD Chronic wasting disease (CWD) is a fatal transmissible spongiform encephalopathy(TSE) affecting cervids that continues to expand geographically across North America and into new host populations. Sustained transmission of CWD in free-ranging cervids is driven by efficient horizontal spread through environmental contamination and host shedding; however, the cellular and molecular mechanisms that govern prion trafficking within the host and facilitate dissemination between individuals remain incompletely understood. In particular, mechanisms underlying hematogenous peripheralization of prions and the contribution of vertical transmission at the maternal-fetal interface remain important but poorly defined components of CWD ecology. The overall objective of this dissertation was to investigate mechanisms of prion trafficking and transmission in CWD, with a focus on vertical transmission pathways, the development of improved histologic diagnostic approaches capable of detecting low-abundance prion deposition in tissues, and extracellular vesicle (EV)-mediated dissemination. Given the growing evidence that hematogenous dissemination plays a central role in the pathogenesis and transmission of CWD, the first objective of this work was to investigate mechanisms of maternal-fetal prion transfer within this systemic framework. Circulating prions within blood and blood-derived compartments, including EVs, represent a plausible route linking peripheral infection to both tissue tropism and vertical transmission. To address this, I employed a well-established Reeves’ muntjac (Muntiacus reevesi) infection system to examine prion distribution at the maternal-fetal interface during pregnancy, with particular emphasis on tissues positioned at the interface of maternal circulation and fetal exposure. A key component of this work was the development, optimization, and application of a highly sensitive immunohistochemical approach, amplified immunohistochemistry (AMP-IHC), designed to enhance detection of low-abundance PrPCWD in formalin-fixed, paraffin-embedded tissues. By improving the visualization of subtle and spatially restricted prion deposition, AMP-IHC provides a key methodological bridge between circulating prion burden and tissue-level localization. Compared with conventional IHC, AMP-IHC employs signal amplification strategies that increase sensitivity while preserving tissue architecture, thereby enabling robust histologic identification of prion deposition at sites relevant to hematogenous spread and potential maternal-fetal transmission. Using this approach, prion immunoreactivity was detected in the uterine glandular epithelium of CWD-infected pregnant muntjac between three and seven months of gestation and five to 26 months post-inoculation. Notably, similar immunoreactivity was also observed in one non-pregnant muntjac. The localization of prion deposition within uterine glands is particularly notable given the well-established role of these structures in secreting histotroph that nourishes the developing conceptus. These findings provide histologic evidence supporting a potential cellular pathway for vertical transmission, whereby prions within uterine glandular secretions could gain access to the developing fetus through trophoblast uptake or other maternal-fetal exchange mechanisms. This finding advances our understanding of how CWD prions may be transmitted during gestation and identifies uterine glands as a previously underappreciated site of prion accumulation at the maternal-fetal interface. The second objective of this dissertation was to evaluate the diagnostic utility of AMP- IHC for improving detection of CWD prions in tissues from free-ranging naturally exposed and infected white-tailed deer (Odocoileus virginianus) (WTD). Current diagnostic methods rely primarily on conventional IHC or enzyme-linked immunosorbent assays (ELISA) targeting lymphoid tissues and the obex region of the brainstem. While these methods are highly specific, detection sensitivity can be limited when prion burden is low or unevenly distributed within tissues. To address this limitation, I applied AMP-IHC to tissues collected from free-ranging WTD and compared patterns of prion deposition with those detected using standard immunohistochemical techniques. The use of AMP-IHC revealed more robust and readily detectable prion deposition in both lymphoid tissues and the obex, enhancing visualization of characteristic prion accumulation patterns and diagnostic efficiency within these target tissues. These results demonstrate that signal-amplified immunohistochemical approaches can improve visualization and diagnostic efficiency of histologic prion detection while maintaining compatibility with routine diagnostic workflows. Extracellular vesicles (EVs) have emerged as mediators of intercellular communication and have been implicated in the propagation of several neurodegenerative proteinopathies. Prior studies in other prion systems have suggested that EVs may serve as carriers of infectious prions, facilitating hematogenous transport and cellular transmission. To evaluate whether EVs contribute to the peripheral dissemination of CWD prions, the final objective of this dissertation was to investigate the association between prions and serum and plasma-derived EVs using sensitive in vitro prion amplification assays. EV populations were isolated from WTD serum and plasma and characterized using various techniques prior to analysis with our lab’s prion amplification assays. These assays can detect extremely low concentrations of amyloid seeding activity (i.e. prions) through the templated conversion of recombinant or native prion protein substrates. Across multiple experimental conditions and biological replicates, I was unable to demonstrate an association between EVs and detectable CWD prion seeding activity. While positive controls consistently demonstrated assay sensitivity, terminally collected, blood-derived EV preparations from late stage CWD-infected WTD did not yield reproducible amplification signals above background levels. These results refine our understanding of prion distribution in peripheral biofluids and suggest that, under the conditions tested, circulating EVs are not a major reservoir of detectable prion seeding activity in blood during clinically terminal CWD infection. In addition, these findings highlight the importance of critically evaluating proposed mechanisms of prion dissemination using in vitro highly sensitive molecular detection platforms. Collectively, the studies presented in this dissertation address key gaps in our understanding of CWD prion transmission, with particular emphasis on vertical transmission and improved detection of prions at the maternal-fetal interface. The identification of PrPCWD deposition within uterine glandular epithelium provides new evidence supporting a potential route of maternal-fetal interface involvement in prion dissemination and vertical transmission. In parallel, the application of AMP-IHC highlights the value of enhanced diagnostic ability in detecting low-level prion accumulation in both experimental and field-derived tissues. To explore potential mechanisms of systemic dissemination, this dissertation also investigated EVs as a blood-borne carrier of prions. However, assessment was limited to a terminal disease time point, and no association was detected between EV preparations and amyloid seeding activity, suggesting that EV-associated prion carriage may not be a dominant feature at this stage of disease or may vary across stages of infection. Together, these findings provide a structured framework for understanding CWD pathogenesis by first defining sites of prion accumulation relevant to vertical transmission, then demonstrating the utility of sensitive amplification-based diagnostics and finally evaluating a potential circulatory transport mechanism. While further longitudinal studies are required to define temporal dynamics of prion trafficking, these results collectively contribute to a more comprehensive understanding of tissue-specific prion distribution and improve methodological approaches for prion detection and surveillance in cervid populations.
Keywords: Chronic Wasting Disease; Hematogenous; Vertical Transmission; Extracellular Vesicles; Amplification-Immunohistochemistry; Prion